Some roughness results concerning reducibility for linear difference equations - Garyfalos Papaschinopoulos (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove first that the exponential dichotomy of linear difference equations is rough. Moreover we prove that if the coefficient matrix of a linear difference equation is almost periodic, then the Joint property of having an exponential dichotomy with a projection P and being reducible with P by an almost periodic kinematics similarity is rough.